Optimizing the Utilization of Egg Shell Waste for the Production of Liquid Organic Fertilizer in Trangsan Village, Gatak, Sukoharjo: Improving Welfare and Environmental Sustainability: Optimalisasi Pemanfaatan Limbah Cangkang Telur untuk Produksi Pyupuk Organik Cair di Desa Trangsan, Gatak, Sukoharjo: Meningkatkan Kesejahteraan dan Keberlanjutan Lingkungan - Putri, Nita Kusuma; Winarno, Bowo; Setiawan, Fardian Putra Dwi; Hidayatullah, Fathan Syarif; Dananjaya, Muda Kusuma; Azqiyah, Naili; Rafii’, Nasywa ‘Athiyyatur; Syahidah, Syauqina Naila; Kinasih, Syradennita Ayu; Sari, Zahra Atikah; Hapsari, Zahra Aulia (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The increasing volume of organic waste, including eggshells, poses significant environmental challenges. Trangsan Village, Sukoharjo, is one area with abundant eggshell waste due to poultry hatching activities. This study aims to optimize the utilization of eggshell waste by processing it into eco-friendly liquid organic fertilizer (LOF). Eggshells containing 97–98.5% calcium carbonate (CaCO₃) were processed into liquid fertilizer through fermentation using EM-4 bioactivators. The program involved stages such as public socialization, fertilizer-making simulation, laboratory testing, and dissemination of results to farmers. Laboratory results revealed the fertilizer contains 1.11% organic carbon (C-organic), 0.23% nitrogen, and 0.19% potassium. However, nitrogen and potassium levels require further optimization. Community socialization demonstrated high enthusiasm, particularly in repurposing household waste into valuable resources. This initiative offers economic opportunities and supports environmental sustainability by reducing organic waste and reliance on chemical fertilizers.